(untitled) (Perner’s Contacts, 2020)
The technologies of vehicle automation are constantly evolving to make vehicles more efficient. The vehicle approval legislation must allow this innovation while ensuring road safety, cyber security etc. Autonomous vehicles are therefore not only a challenge for vehicle manufacturers, but also for the approval authorities themselves, which authorize vehicles for road traffic. An internal market that promotes new technologies and at the same time protects citizens from the new risks posed by self-driving vehicles must be guaranteed. New technologies not foreseen in the current legislation can be approved on the basis of a derogation granted under a national ad hoc safety assessment. In this way, level 3 and 4 autonomous vehicles can currently be approved for road traffic. Level 3 and 4 vehicles are already being tested and are expected to be available.